THE ROLE OF ORGANIZATIONAL AGILITY IN CREATING LEARNING ORGANIZATION (AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN THE HEALTH CARE CENTER IN THE ABBAS NEIGHBORHOOD IN THE HOLY CITY OF KARBALA) - Muntadher Kadhim Shamran; Abeer M. Mahdi AL-shammari; Mohsin Abbood Bandar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The main objective of the study is to find a relationship of correlation and influence of organizational agility with the learning organization, and the study was conducted at the Primary Health Care Center in Al-Abbas neighborhood in the holy city of Karbala to find out the level of opinions and understanding among workers about the variables of the study. The main hypotheses of the study were the correlation and effect between the variables and determining the effect of the sample demographics on the dependent variable. The questionnaire was used as a study tool in collecting the required data, and the study reached the fact that there is a strong positive correlation between the dimensions of the organizational agility with the learning organization, as for the effect relationships between the study variables, they were of insignificant value.